Physical and chemical observations in marine stratus during the 1993 North Atlantic Regional Experiment: Factors controlling cloud droplet number concentrations - Leaitch, W. R.; Banic, CM; Isaac, GA; Couture, MD; Liu, P. S. K.; Gultepe, I; Li, S. M.; L. Kleinman; Daum, PH; MacPherson, JI (JOURNAL OF GEOPHYSICAL RESEARCH-ATMOSPHERES, 1996)
Airborne observations from 14 flights in marine stratus over the Gulf of Maine and Bay of Fundy in August and September of 1993 are examined for the relationships among the cloud droplet number concentrations (Nd), the out-of-cloud aerosol particle number concentrations (N-a), the major ion concentrations in the cloud water, and turbulence in cloud. There was a wide range of aerosol concentrations, but when low stratus and the main anthropogenic plume from eastern North America were in the same area the plume overrode the cloud. The N-d increased with increasing N-a and cloud water sulfate concentration (cwSO(4)(=)), but the relationships were very weak. The separation of the data between smooth and lightly turbulent air substantially improved the ability to explain the variance in the N-d by either of these two quantities. Also, the relative increase in N-d for increases in N-a and cwSO(4)(=) was greater for lightly turbulent air than for smooth air. The estimated minimum size of particles activated in these clouds ranged from 0.14 mu m to 0.31 mu m, corresponding to average supersaturations of <0.1%. The minimum size tended to be lower for lightly turbulent air and smaller N-a. The results for lightly turbulent air agree well with previously reported parameterizations of the impact of aerosols on N-d, but the results for smooth air do not agree. In general, more knowledge of the physical factors controlling the N-d in stratiform clouds, such as turbulence, is needed to improve not only our ability to represent N-d but also to increase our understanding of the impact of the aerosol particles on the N-d and climate.